PENDIRIAN PERPUSTAKAAN DESA UNTUK PENINGKATAN LITERASI MASYARAKAT DESA BAWU BATEALIT JEPARA - Fathur Rohman; Yushinta Eka Farida; Muhammad Muslih; Rizahul Ilham (LPPM Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2024)
This article aims to describe a community service program by establishing a village library to increase the literacy of the people of Bawu village, Batealit, Jepara. There are two problems studied in this paper, namely 1) How to establish a village library to increase the literacy of the Bawu village community? 2) what are the results of the program? This program is implemented using the Participatory Rural Appraisal (PRA) method with stages: a) problem identification b) planning c) implementation d) monitoring e) evaluation. The result of this program was the establishment of the Bawu Batealit Jepara village library, which was named the